A Mirror Representation of Others' Actions in the Human Anterior Parietal Cortex - Shmuelof, Lior (J Neurosci, 2006)
The anterior part of the human intraparietal sulcus is known to be involved in visually guided grasping. This region is also active during the observation of object manipulation by others. Here, we explore the nature of action representation using functional magnetic resonance imaging (fMRI). Fourteen subjects observed video clips showing object manipulation by the right or left hand . The clips were presented in either the right or left peripheral visual field. The fMRI activation in the occipital cortex and in the caudal sections of the parietal cortex was specific to the visual-field location of the clips. In contrast, the principal factor determining the response in anterior intraparietal cortex was the identity of the observed hand. Furthermore, these “hand-specific” parietal areas also showed contralateral hand specificity during self action (i.e., object manipulation) without visual feedback. A similar selectivity for the identity of the observed hand was seen when using a region of interest analysis, focusing on individually defined visuomotor voxels within the parietal cortex. This dual visuomotor grasping representation lends further evidence for the existence of a mirror system in humans and suggests that the anterior intraparietal cortex is involved in the specific motor simulation of hand actions.